The Efficacy of Transcarotid Artery Revascularization With Flow Reversal System Compared to Carotid Endarterectomy: A Systematic Review and Meta-Analysis - Gao, Jianfeng; Chen, Zhong; Kou, Lei; Zhang, Hanfang; Yang, Yaoguo (Frontiers in Cardiovascular Medicine, 2021)
Background: Carotid artery stenosis has long been a critical cause of stroke and death, and it can seriously affect the life quality. Transcarotid artery revascularization (TCAR) and carotid endarterectomy (CEA) are both feasible therapies for this disease. This systematic review and meta-analysis aims to evaluate if the efficacy of the two approaches are comparable. Methods: Clinical studies up to March 2021 were searched through Pubmed, Embase and Scopus from computer. The screening process was designed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Newcastle-Ottawa Scale (NOS) was used for methodological quality assessment of literatures meeting the inclusion criteria, and Review manager 5.3 was used for data synthesis. I2 statistic was performed to measure the heterogeneity, and M-H fixed or random model was utilized depending on the I2 value. The evidence evaluation was accomplished based on GRADE online tool. Results: A total of 14,200 subjects (6 comparative studies) were finally included in this pooled study. There is no statistical discrepancy between the two treatments on reducing stroke/death/myocardial infarction (OR 0.85, 95% CI 0.67-1.07), stroke (OR 1.03, 95% CI 0.77-1.37) or death (OR 1.14, 95% CI 0.67-1.94). Besides, TCAR is associated with lower incidence of myocardial infarction (P=0.004) and cranial nerve injury (P＜0.0001) than CEA among overall cohort. Conclusions: TCAR is a rapidly developing treatment reaches comparable prognosis to CEA, which is a dependable choice for patients with carotid stenosis.